Prevention of cervical cancer: epidemiological profile of cytopathological exams performed in the municipality of Pinheiro, Maranhão, from 2016 to 2020 (Research, Society and Development, 2022)
Objective: To evaluate the epidemiological profile of cervical cytopathological exams registered in the Cancer   Information System (SISCAN) from 2016 to 2020 in the municipality of Pinheiro, Maranhão. Method: A descriptive, retrospective, epidemiological study with a quantitative approach. The following variables were analyzed: age range, number o of    cytopathological exams performed in the study period, type of cervical and cervicovaginal cytological changes, sample adequacy, and reason for the exam. The data were categorized, tabulated in Microsoft Excel version 2019, and   arranged in graph and tables. Results: 11. 636 preventive examinations were recorded, the largest quantity belongs to the age group 35 to 44 years , sample suitability presented the total of 99.43 % keeping a significant index in the temporal analysis, screening was the main indicator for performing the cytopathological examination with 98, 79 % , and the main changes were benign reactive/reparative inflammation type, cervical cytological changes in squamous cells with greater frequency comprise the Low-grade Squamous Intraepithelial Lesion (LSIL) and Atypia of Undetermined Significance/possibly non-neoplastic (ASC-US) respectively. Conclusion: This study denotes the importance of the effectiveness of screening programs, especially regarding the analysis of test results and the follow-up of the target population screened for cervical cancer prevention.